Making boundaries permeable: the university experience through the social sciences - Wardrop, Joan; Hilsden, Anne-Marie; Moore, Philip (Curtin University, 2012)
In this paper we reflect on the challenges of developing and teaching two new first-year (intensively inter/cross-disciplinary and online learning focussed) and two third-year units (more traditional capstone and discipline-based seminar/workshops) in the Department of Social Sciences at Curtin University in a time of significant change to both structural and institutional frameworks. We interrogate our discursive understandings of student responses to units which subvert expectations and demand that students become border crossers (often of self-constructed barriers). In describing and analysing several of the strategies used in the spiral development of skills such as persuasive argument, image-word narratives and cultural accounts, and the ways in which online technologies can be deployed to make these strategies possible, we seek to understand the complexities of the demands felt by students (and staff) as we enter the foreign culture of the 21st century university.